2019
DOI: 10.1590/0001-3765201920181257
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Vitamin C on Triptolide-induced Acute Hepatotoxicity in Mice through mitigation of oxidative stress

Abstract: Triptolide, a purified diterpenoid from the herb Tripterygium wilfordii Hook.f., was widely used to treat many diseases. However, the hepatotoxicity of triptolide limited its clinical use. Research showed oxidative stress played an important role in triptolide-induced liver injury. To investigate the effect of vitamin C, which was one of the most effective antioxidants, on triptolide-induced hepatotoxicity and its potential mechanism in mice. In the present study, acute liver injury was induced by intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…We also found that antioxidants, VC and NAC effectively neutralized the Bmib-induced neurotoxicity. Since both VC and NAC have been reported to protect cells from the oxidative stress observed in cardiac autonomic neuropathy (15), liver injury (16), ischemia reperfusion injury (17) and critical limb ischemia (18), the oxidative stress may be involved in the present Bmib-induced neurotoxicity. Metabolomics and DNA microarray analysis may provide the evidences of oxidative stress that may be involved in the Bmib-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that antioxidants, VC and NAC effectively neutralized the Bmib-induced neurotoxicity. Since both VC and NAC have been reported to protect cells from the oxidative stress observed in cardiac autonomic neuropathy (15), liver injury (16), ischemia reperfusion injury (17) and critical limb ischemia (18), the oxidative stress may be involved in the present Bmib-induced neurotoxicity. Metabolomics and DNA microarray analysis may provide the evidences of oxidative stress that may be involved in the Bmib-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of ROS leads to activation of p53 in cells and antioxidants can reduce ROS levels, preventing the activation of p53 , thereby reducing apoptosis (Gong et al, 2016; Kim et al, 2008). Anti‐oxidants, such as VC, can reduce the expression of the apoptotic marker caspase‐3 during the treatment of certain forms of heart disease, and increase the GSH levels (El‐Shitany & El‐Desoky, 2016; Xu et al, 2019). Decrease in GSH content is a potential early activation signal for apoptosis, and subsequent generation of oxygen free radicals can induce apoptosis (Armstrong et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying a supplement for reducing the hepatotoxicity of PFOA can be helpful for the public. Vitamin C, for example, is an antioxidant commonly for boosting liver function [29] , [30] . In this study, we sought to evaluate the possible protective role of vitamin C on PFOA-induced hepatotoxicity using a mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, vitamin C supplementation was suggested to provide a protective effect on toxicant-induced hepatotoxicity [15] . Moreover, a study on mice showed that vitamin C retarded triptolide-induced acute hepatotoxicity through oxidative stress mitigation [16] . A similar protective effect of vitamin C was reported for fipronil-induced oxidative stress in mouse liver [16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation